ESGO-ESMO-ESP consensus conference recommendations on ovarian cancer: pathology and molecular biology and early, advanced and recurrent disease - Ledermann, Jonathan A.; Matias-Guiu, X.; Amant, F.; Concin, N.; Davidson, B.; Fotopoulou, C.; González-Martin, A.; Gourley, C.; Leary, A.; Lorusso, D.; Banerjee, S.; Chiva, L.; et al. (Annals of oncology, 2024)
The European Society of Gynaecological Oncology, the European Society for Medical Oncology (ESMO) and the European Society of Pathology held a consensus conference (CC) on ovarian cancer on 15-16 June 2022 in Valencia, Spain. The CC panel included 44 experts in the management of ovarian cancer and pathology, an ESMO scientific advisor and a methodologist. The aim was to discuss new or contentious topics and develop recommendations to improve and harmonise the management of patients with ovarian cancer. Eighteen questions were identified for discussion under four main topics: (i) pathology and molecular biology, (ii) early-stage disease and pelvic mass in pregnancy, (iii) advanced stage (including older/frail patients) and (iv) recurrent disease. The panel was divided into four working groups (WGs) to each address questions relating to one of the four topics outlined above, based on their expertise. Relevant scientific literature was reviewed in advance. Recommendations were developed by the WGs and then presented to the entire panel for further discussion and amendment before voting. This manuscript focuses on the recommendation statements that reached a consensus, their voting results and a summary of evidence supporting each recommendation.
Online verfügbar: 1 Februar 2024, Artikelversion: 21. Februar 2024
Gesehen am 21.01.2025